Landscape analysis to identify landforms from images generated by lidar technologies - de Oliveira, Urandir Fernandes; de Lima , Fernanda Maria; Leite, Robson; Nery, Saulo Ivan; de Oliveira , Fernando Silveira (Seven Editora, 2024)
This article presents the analysis of the landscape of peculiar reliefs called "chess", located in the north of the municipality of Apiácas, in the state of Mato Grosso. It is a residual relief from denudational processes typical of the Amazon Craton, identified in the region of the lower course of the Juruena and Teles Pires rivers. The intention is to contribute to the local geomorphological knowledge about the differentiation between drainage patterns and the rectilinear cuts located on the residual plateau of the Apiacás and Sucunduri. The images obtained with LiDAR and the geological and geomorphological information of the region were compared based on secondary data from IBGE surveys and other surveys. Based on the delimitation of sub-basins and micro-basins and observations about the surface circulation of water, it was possible to better understand the local relief. Peculiar structures were identified in the relief and indications that differentiate the drainage pattern with the sections identified in a "checkerboard" format. DOI:https://doi.org/10.56238/sevened2024.018-032